A new strategy to tailor the structure of sustainable 3D hierarchical porous N-self-doped carbons from renewable biomass for high-performance supercapacitors and CO2 capture. Issue 41 (7th April 2016) - Tong, Xing; Zhuo, Hao; Wang, Sha; Zhong, Linxin; Hu, Yijie; Peng, Xinwen; Zhou, Weijia; Sun, Runcang
Abstract : A new method was employed to obtain 3D hierarchical porous N-self-doped carbons with different porous structures from chitosan for high-performance supercapacitors and CO2 capture without using porogens, catalysts or activators. Abstract : Hierarchical porous N-doped carbons show great potential applications in energy storage and CO2 capture. Renewable biomass chitosan, which is abundant and simultaneously contains large amounts of N and C, is an ideal alternative to fossil resources for sustainable and scale-up production of cost-effective N-self-doped carbons. In this work, we employed a new and effective strategy to obtain 3D hierarchical porous N-self-doped carbons from chitosan. The hierarchical porous structure of the N-self-doped carbons could be easily tailored to obtain nanorod interconnected and fiber-wall interconnected architectures without using any porogen, catalyst or activator. The nanorod interconnected porous carbon displayed a high specific surface area of 1408 m 2 g −1 while the fiber-wall interconnected porous carbon exhibited an excellent specific capacitance of 261 F g −1 (0.5 A g −1 ) due to the desirable hierarchical framework. In addition, these hierarchical porous carbons had a good CO2 capture performance (3.07–3.44 mmol g −1 at 25 °C). This unique method is supposed to be a new strategy to create novel 3D hierarchical porous carbons for promising applications in supercapacitors, lithium ion batteries, fuel cells and sorbents.